Women's experiences of pain management during childbirth at Bwaila Hospital in Lilongwe, Malawi - Phiri Kachapila, Isabel (2021)
Childbirth pain is one of the most severe pains which have ever been evaluated. Most women perceive childbirth pain as the most severe and distressing event of a woman’s existence. There are negative effects of unmanaged labour pain on both mother and foetus. Hence, both pharmacological and non-pharmacological pain relief approaches are vital to relieve childbirth pain. However, evidence shows that utilization of pain relief measures during childbirth is very low in Sub Saharan Africa which includes Malawi. Furthermore, women’s experiences of childbirth pain and how they cope with pain have not been adequately explored in Malawi. Hence, a descriptive qualitative study was conducted to explore women experiences of pain management during childbirth at Bwaila Hospital. In-depth interviews were conducted with 15 postpartum participants who were recruited using purposive sampling after obtaining clearance from College of Medicine Research and Ethics Committee and consent from participants. Data were audio recorded and field notes were taken to complement the recorded data. Narratives were analysed using content analysis. The findings revealed that women experienced intense pain on their back and lower abdomen during childbirth. Some women did verbalize the pain while others used nonverbal communication. The study also identified aggravating and alleviating factors of pain during childbirth. However, participants were not given any pharmacological pain relief measure during childbirth to relieve them from their intense pain which they experienced. Some participants were only advised on what to do when feeling severe pain. Their pain was not managed according to their expectations hence ending up not to be satisfied with the pain management. As such, recommendations to the nurse in charge to organize Continuing Professional Development sessions for midwives and managers to support with adequate human resource in Maternity have been made.